2023
DOI: 10.3389/fchem.2023.1162412
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for the modulation of mechanosensitive MscL channel pores

Abstract: MscL was the first mechanosensitive ion channel identified in bacteria. The channel opens its large pore when the turgor pressure of the cytoplasm increases close to the lytic limit of the cellular membrane. Despite their ubiquity across organisms, their importance in biological processes, and the likelihood that they are one of the oldest mechanisms of sensory activation in cells, the exact molecular mechanism by which these channels sense changes in lateral tension is not fully understood. Modulation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…This assumption is supported by our findings that a mutant strain of S. aureus lacking the mscL gene remained sensitive to xanthorrhizol, but at concentrations higher than those observed for the wild-type strain ( Figures 3A , 4B ). Xanthorrhizol appears to share some of its antimicrobial properties with curcumin, which also limits bacterial growth in a MscL-dependent manner and increases the activity of MscL channels, possibly due to changes in biophysical properties of the membrane, for example by its thinning, since the direct binding site for curcumin has not been identified ( Wray et al, 2021 ; Lane and Pliotas, 2023 ). Curcumin, a flavonoid polyphenol isolated from rhizome of turmeric ( Curcuma longa L.) ( Teow et al, 2016 ), which is active against both gram-negative and gram-positive bacteria, but its activity against S. aureus is less than that of xanthorrhizol ( Teow et al, 2016 ; our unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is supported by our findings that a mutant strain of S. aureus lacking the mscL gene remained sensitive to xanthorrhizol, but at concentrations higher than those observed for the wild-type strain ( Figures 3A , 4B ). Xanthorrhizol appears to share some of its antimicrobial properties with curcumin, which also limits bacterial growth in a MscL-dependent manner and increases the activity of MscL channels, possibly due to changes in biophysical properties of the membrane, for example by its thinning, since the direct binding site for curcumin has not been identified ( Wray et al, 2021 ; Lane and Pliotas, 2023 ). Curcumin, a flavonoid polyphenol isolated from rhizome of turmeric ( Curcuma longa L.) ( Teow et al, 2016 ), which is active against both gram-negative and gram-positive bacteria, but its activity against S. aureus is less than that of xanthorrhizol ( Teow et al, 2016 ; our unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanosensitive channel of large conductance (MscL), which protects bacteria against strong osmotic variations, is a prototype of mechanosensitive protein channels [68] . Although it was suggested that the protein senses variations of membrane thickness, [69] the exact mechanism by which MscL is activated is not fully understood [70] . In an early study, it was found that the isomerization of di‐(5‐{[4‐(4‐butylphenyl)azo]phenoxy}pentyl)phosphate (4‐Azo‐5P), in which both acyl chains are functionalized with an azobenzene group (Figure S2C), can increase the opening probability of MscL in a reversible manner following long irradiation times (30–140 seconds) [71] .…”
Section: Azobenzene‐derived Photo‐lipidsmentioning
confidence: 99%
“…[68] Although it was suggested that the protein senses variations of membrane thickness, [69] the exact mechanism by which MscL is activated is not fully understood. [70] In an early study, it was found that the isomerization of di-(5-{[4-(4-butylphenyl)azo]-phenoxy}pentyl)phosphate (4-Azo-5P), in which both acyl chains are functionalized with an azobenzene group (Figure S2C), can increase the opening probability of MscL in a reversible manner following long irradiation times (30-140 seconds). [71] Later on, Booth and co-workers [72] reconstituted MscL in DOPC/DOPG (1 : 1, w/v) lipid vesicles doped with up to 10 % (w : v) of 4-Azo-5P.…”
Section: Impact Of Photo-lipids On Membrane Proteinsmentioning
confidence: 99%